Kapasitas Kelembagaan Pemerintah Desa dalam Perencanaan Pembangunan Desa - Ghazi Qinthara Al Giffari, Muhammad; Sukarno, Dedi (Jurnal Ilmiah Administrasi Publik, 2024)
This research discusses the institutional capacity of Tanjungsari Village Government in enhancing economic resilience through village development planning. The study aims to reconstruct the concept of institutional capacity of village governments in development planning using the Salvador & Sancho (2021) concept. The method used is descriptive qualitative. Primary data were obtained from in-depth interviews and direct observations, while secondary data were collected from books, journals, and related legal regulations. The research findings indicate several aspects that support the role of the village government, namely related to strategic capacity, analytical capacity, management capacity, and collaborative capacity. Overall, the Tanjungsari Village Government has not fully demonstrated strong institutional capacity in conducting village development planning. This is particularly evident in the implementation of analytical and management capacity aspects. In addition to the resources available, analytical capability and the completeness of village data also have limitations in both usage and quality and quantity. However, there are several components that serve as strengths, such as strategic leadership, budget allocation, data units, coordination systems, and efforts to enhance collaboration. With appropriate improvements, it is hoped that the development planning of Tanjungsari Village can become more effective and have a positive impact in accordance with the constitutional mandate to improve the welfare of the community.